Embedded research in energy innovation: An examination of cases and theories of knowledge creation for power generation and lighting technologies. (October 2019) - Foord, David; McLaughlin, John D.
Abstract: This article examines the association of location and actors in the invention, development and innovation of power generation and lighting technologies. It is known that niche actors play important roles in knowledge creation and energy innovation. What is not well understood is the association and influence of location for sustainability transition knowledge creation. To understand the association of location and knowledge creation we use a theoretically novel framework which integrates concepts of niches, mode 2 knowledge production, embedded research and socio-spatial embedding. We applied the new framework and comparative case study methods to answer our research question of what locations and actors are associated with knowledge creation. We found that knowledge creation in the cases is positively associated with locations-of-use and the involvement of niche actors. The spacial and temporary variation of our cases limits the generalizability of our framework. Future research directions include examination of other historical and contemporary case studies, and identification of effective practices in embedding energy knowledge creation projects in locations-of-use.